S125 Relationship of right heart echo parameters to functional status and pulmonary function in severe COPD. (12th November 2015) - Liu-Shiu-Cheong, PSK; Lipworth, BJ; Goudie, AR; Short, PM; Hopkinson, PJ; Struthers, AD
Abstract : Introduction: COPD is associated with structural and functional cardiac changes, particularly the right heart. There is little evidence as to whether right heart echo parameters are associated with QOL, health status and pulmonary function. Methods: We looked at the relationship of right heart function to QOL (SGRQ) and health status (SF-36) and to pulmonary function (spirometry and DLCO) in patients with severe COPD. Results: 120 patients were included in the analysis: 82 men and 38 women; mean age 69 years; mean FEV1 41%; mean FEV1/FVC 0.38; mean PAP 29 mmHg; mean Sa02 95%. Pulmonary vascular resistance was related to 6MW distance (p = 0.008), BODE Index (p = 0.01) as well as FVC% (p = 0.03). RV ejection time (RVET) was related to SGRQ (p = 0.02), SF-36 scores for limitations due to physical problems (PL) (p = 0.03), social functioning (SF) (p = 0.04) and general health perceptions (GH) (p = 0.02) as well as FVC% (p < 0.001) and DLCO (p = 0.001). When comparing pulmonary acceleration time (PAT) <100 ms (n = 68) vs PAT ≥ 100 ms (n = 51), we found a difference in mean SGRQ 59.3 vs 52.1 (p = 0.01) and mean RVET 262 vs 286 ms (p = 0.001). Dynamic lung volumes as FEV1 %, FVC% and FEV1 /FVC were significantly related to SGRQ and SF-36 scores for physical function (PF), PL, SF and GH. There were significant differences between GOLD 2 vs GOLD 4 groups for: mean PAP (p = 0.05), mean RVET (p = 0.001) and mean SF-36 scores for PF (p < 0.001), PL (p = 0.009), SF (p = 0.01) and GH (p = 0.001). Conclusion: In patients with severe COPD, right heart echocardiographic parameters are associated with functional status and dynamic lung volumes.